1994
DOI: 10.1007/bf02087653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α1-adrenergic blockade on canine ileal water, electrolyte, and glucose absorption

Abstract: Meal ingestion stimulates an increase in small intestinal water and electrolyte absorption. Endogenous norepinephrine may at least partially mediate this meal-stimulated proabsorptive response. Luminally administered alpha 1-adrenergic agonists such as norepinephrine and phenylephrine cause significant small bowel absorption, which can be prevented by the selective alpha 1-adrenergic antagonist terazosin. This study tested two hypotheses: (1) a meal stimulates ileal water, electrolyte, and glucose absorption; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Results are expressed as mean ± SE, n = 5-9. guinea pig jejunum. Although it has been suggested that both αand βadrenergic receptors mediate transport (Barry et al 1994a(Barry et al , 1994bDiaz-Sampedro et al 1998;Vieira-Coelho and Soares-da-Silva 1998), the distribution of α 1 -and βadrenergic receptors is poorly characterized. Dopamine increases absorption in both in vivo (Barry et al 1995;Donowitz et al 1983;Sjovall et al 1984;Wahawisan et al 1985) and in vitro models (Donowitz et al 1982), and receptors for dopamine have been localized to the intestinal mucosa (Hernandez et al 1987;Marmon et al 1993), including the villus and crypt epithelium (Vaughan et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Results are expressed as mean ± SE, n = 5-9. guinea pig jejunum. Although it has been suggested that both αand βadrenergic receptors mediate transport (Barry et al 1994a(Barry et al , 1994bDiaz-Sampedro et al 1998;Vieira-Coelho and Soares-da-Silva 1998), the distribution of α 1 -and βadrenergic receptors is poorly characterized. Dopamine increases absorption in both in vivo (Barry et al 1995;Donowitz et al 1983;Sjovall et al 1984;Wahawisan et al 1985) and in vitro models (Donowitz et al 1982), and receptors for dopamine have been localized to the intestinal mucosa (Hernandez et al 1987;Marmon et al 1993), including the villus and crypt epithelium (Vaughan et al 2000).…”
Section: Discussionmentioning
confidence: 99%